RECLAMATION COST CALCULATION OF PT. X IN SORONG CITY, SOUTHWEST PAPUA PROVINCE: PERHITUNGAN BIAYA REKLAMASI PT. X KOTA SORONG PROVINSI PAPUA BARAT DAYA - Sinaga, RInda Wati Iriani (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2024)
Reclamation is an effort carried out throughout the mining process to organize, restore, and enhance the quality of the environment and ecosystem, so that the area can function again according to its intended purpose. In the mining industry, companies are required to conduct reclamation. Before carrying out reclamation, the company must calculate the required reclamation costs. PT. X is one of the companies engaged in andesite mining, which is administratively located in Saoka Village, Maladumes District, Sorong City, Southwest Papua Province. After completing the mining activities, PT. X will carry out reclamation by planting pine trees during the period from 2024 to 2028. Based on this, it is necessary to calculate the reclamation costs to determine the expenses the company will incur for this activity. The reclamation cost calculations are based on the Minister of Energy and Mineral Resources Decree Number 1827/K/30/MEM/2018, which outlines the guidelines for implementing Good Mining Engineering Principles. Reclamation costs consist of both direct and indirect costs. Based on the research findings, the total direct and indirect costs that PT. X must incur for reclamation activities from 2024 to 2028 are IDR 359,238,257 and IDR 119,972,490, respectively. Therefore, the total reclamation costs PT. X will incur for the reclamation activities from 2024 to 2028 amount to IDR 479,210,747